2004
DOI: 10.2106/00004623-200406000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Combined Conservative and Orthotic Management of Acute Ruptures of the Achilles Tendon

Abstract: Background: There has been considerable debate about the best treatment for acute rupture of the Achilles tendon. At our institution, a well-documented and structured program of nonoperative management of Achilles tendon rupture with use of casts and a removable orthosis was developed. Methods: We assessed the results in 140 consecutive patients with a complete rupture of the Achilles tendon who had been treated with our nonoperative regimen at our center between 1992 and 1998. Patients were evaluated on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 21 publications
2
58
1
1
Order By: Relevance
“…12 These resulted in good functional outcome, 13 low re-rupture rate, 11,13,14 and even faster healing rate than those managed by operative repair of acute Achilles tendon rupture. 14 Recently, there have been an increasing number of reports suggesting that therapeutic ultrasound promotes tendon healing after open repair. [15][16][17] Enwemeka and colleagues 16 suggested that the beneficial effects of ultrasound were more promising when it was applied at lower intensities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 These resulted in good functional outcome, 13 low re-rupture rate, 11,13,14 and even faster healing rate than those managed by operative repair of acute Achilles tendon rupture. 14 Recently, there have been an increasing number of reports suggesting that therapeutic ultrasound promotes tendon healing after open repair. [15][16][17] Enwemeka and colleagues 16 suggested that the beneficial effects of ultrasound were more promising when it was applied at lower intensities.…”
Section: Introductionmentioning
confidence: 99%
“…2,10 Recently, functional bracing is used as an alternative for immobilization in conservative treatment, which allows early mobilization during rehabilitation. [11][12][13][14] The treatment protocols include 3-4 weeks of cast immobilization and 4-5 weeks of removable orthosis 11,13,14 or cast immobilization at the early phase of healing followed by the use of dosiflexion restricted orthosis, which allows early ankle movement. 12 These resulted in good functional outcome, 13 low re-rupture rate, 11,13,14 and even faster healing rate than those managed by operative repair of acute Achilles tendon rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Ce résultat est sensiblement meilleur qu'en utilisant un traitement non chirurgical qui peut atteindre un taux de rerupture de 6 à 10 % [10][11][12].…”
Section: Discussionunclassified
“…Advances in nonoperative treatment have included both early weightbearing and functional bracing. 62,82,92 Advances in operative management have included suture technique, 48,60,93 percutaneous repair, 3,8,27,32,33,34,47,54,57,81,94 mini-open repair, 5,12,74 and accelerated postoperative rehabilitation. 14,59,60,66 Additionally, several recent meta-analyses and quantitative reviews have compared nonoperative and operative treatment.…”
Section: History Of the Conditionmentioning
confidence: 99%